Pembuatan Plang Petunjuk Rumah Ketua RT dan RW untuk Memudahkan Administrasi Warga Setempat Desa Jogosatru Kecamatan Sukodono Kabupaten Sidoarjo - Novita Faramedina; Nabila Ainun Nadhiah; Sebastianus Priambodo; Mohammad Djaelani; Yayu Sriwahyuni Hamzah; Didit Darmawan; Judiono Judiono (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Jogosatru Village, Sukodono Sub-district, Sidoarjo Regency, identified a major problem related to the lack of adequate facilities, especially related to the house signs of the RT and RW heads. These signs are important as a guide for newcomers to facilitate navigation within the village and also facilitate administrative processes, such as obtaining licenses. To overcome this problem, KKN group 09 students from Sunan Giri University Surabaya have created a program to provide and install information signs for RT and RW houses. The activity began by conducting a field survey to determine strategic locations to install signboards. Once the location was determined, the next step involved drafting the signage, purchasing tools, and acquiring the necessary materials. The process consists of stages from planning to installation of the signs, with the aim of improving accessibility and administrative efficiency for Jogosatru Village residents.